ADVANTAGES OF STEM EDUCATION IN THE EDUCATION OF PRESCHOOL CHILDREN (Academia Science Repository, 2023)
This article describes the purpose of STEM education, STEM education and its advantages in educating preschool children, and the importance of STEM education in the formation of basic skills in children.